СИПОҲСОЛОР БАКР ФАРҒОНИЙ (Scientific journal of the Fergana State University, 2023)
This article describes for the first time the activity of the commander Bakr Fergani, who had a separate place in the Samanid state in the middle of the X century, on the basis of historical sources.